Guitar Deconstruction 17 Tones Raden Machjar - Surya, Ibrahim Adi (CENTRAL ASIA AND THE CAUCASUS, 2022)
Guitar 17 tone is believed Raden Machjar can include western music tone and karawitan tone. In general, the guitar that is used at this time is a guitar that only contains the tone of western music, Thus this paper will focus on the difference from the 12-tone guitar with 17-tone guitar with views of the fret scale size and basic techniques to play it. This research uses qualitative method with derrida deconstruction theory used to discuss Machjar raden thinking. The data obtained will be presented in the form of descriptive analysis.